A User-Friendly Sign Language Chat - Fudickar, Sebastian; Nurzynska, Karolina (International Conference on Interactive Collaborative Learning (ICL), 2007)
The introduced concept of a gesture based sign language chat enables the communication of hearing impaired people over networks, including concerns regarding low throughput and bandwidth characteristics. Existing applications handle that task not appropriate, since either high bandwidth networks are necessary or the extensibility of the vocabulary is complicated for untrained users. Thereby our approach facilitates existing image recognition techniques for the determination of gestures which are captured by a standard camera. The recognised gestures then are mapped to a gesture Id that is transferred to the participants, where it is rendered. Additionally, the uncomplicated extension of the vocabulary by the users is supported. Therefore a centralised server updates the locally stored dictionaries, if necessary.